1987
DOI: 10.1111/j.1365-2044.1987.tb02986.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung water during the puerperium

Abstract: Summary An alteration in pulmonary water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…13 Pregnant patients are more susceptible to pulmonary edema due to increased pulmonary capillary permeability. 20 In our study we have found no significant difference in the incidence of hypotension and CVSE among the two groups. Our observation is similar to previous studies.…”
Section: Results and Observationcontrasting
confidence: 51%
“…13 Pregnant patients are more susceptible to pulmonary edema due to increased pulmonary capillary permeability. 20 In our study we have found no significant difference in the incidence of hypotension and CVSE among the two groups. Our observation is similar to previous studies.…”
Section: Results and Observationcontrasting
confidence: 51%
“…administration causes a signi®cant increase in central venous pressure, 55 pulmonary wedge pressure 78 and haemodilution, 136 with possible detrimental consequences from increased lung water content. 75 A more rational approach may therefore be the use of vasopressors instead of a highvolume preload during regional anaesthesia. A randomized study comparing an ephedrine infusion with a 15 ml kg ±1 crystalloid infusion in 54 patients undergoing elective gynaecological surgery with spinal anaesthesia, reported a signi®cantly lower incidence of hypotension with the ephedrine infusion (22 vs 55%).…”
Section: Regional Anaesthesiamentioning
confidence: 99%
“…During pregnancy, pulmonary vascular pressures alter little, but the hydraulic conductivity of the alveolarcapillary membrane increases and plasma oncotic pressure decreases (MacLennan 1986). These changes would be expected to cause an increase in total lung water during pregnancy, and this has been shown to be the case (MacLennan et al 1987). Beta-sympathomimetic agents appear to act by increasing the permeability of the alveolar-capillary barrier, and in one report of fatal pulmonary oedema precipitated by ritodnne, total lung water was found to be five times the normal value (MacLennan et al.…”
Section: Discussionmentioning
confidence: 97%